A novel method for determining the spatial responses of a cable-stayed bridge with four cable-planes. (1st February 2019) - Yuan, Peng; Cai, C.S.; Li, Dejian; Xu, Guoji; Li, Chuanxi
Highlights: A novel method for determining the spatial responses for cable-stayed bridges is proposed. This method can efficiently optimize the structural spatial responses of the bridge. The plane and spatial responses for the prototype bridge at the design stage are discussed. The stress envelope diagram and time-history curve at the construction stage are investigated. Abstract: In this paper, a novel method for determining the spatial responses of a cable-stayed bridge with four cable-planes at the design and construction stages is proposed. Herein, the entire construction stage includes many intermediate steps and one completion step. In this method, the spatial responses of the bridge at the design stage (SRBDS) are firstly determined by minimizing the bending and torsion strain energy of the cable-stayed bridge. Simultaneously, the optimal cable forces and the ratios of the inside to outside plane cables are also determined at this stage. Note that the SRBDS are considered as the target responses of the construction stage at the completion step. Then, the Forward process method is used to calculate the spatial responses of the bridge at the construction stage (SRBCS). The least square method is employed to minimize the difference values of the selected control parameters, e.g., cable forces and displacement, between the completion step at the construction stage and the design stage. Finally, the revised results, which satisfy the designated error requirements, are preserved as the SRBCS. To verify the proposed method, an example cable-stayed bridge with four cable-planes and double-girders, the Jiashao bridge, is analyzed. The structural responses, e.g., the stress and displacement of the girder and tower, of the bridge at the design and construction stages are analyzed and compared to demonstrate the superiority of the proposed method and investigate the spatial responses, e.g., the torsion in the main girder, of this cable-stayed bridge with four cable-planes.